Long-term trends in World Bank rule-based supervision: overcoming the yes-men culture - Zapatero Miguel, Pablo (CUADERNOS DE DERECHO TRANSNACIONAL, 2013)
Abstract: The World Bank lending policies and procedures are under increasing social pressure.Local communities and civil society activists demand transparency and accountability in development projects.The establishment of the Inspection Panel is a critical policy change in this direction, transformingthe inner dynamics of the Bank´s decision-making processes. Notwithstanding this significant advance,additional reforms are required in order to mainstream human rights law in policies and procedures. Key words: World Bank, Inspection Panel, projects, transparency, accountability, rules andprocedures. Resumen: Las políticas y procedimientos del Banco Mundial están sometidas a una crecientepresión social. Comunidades locales y activistas de la sociedad civil demandan transparencia y responsabilidaden los proyectos de desarrollo. El establecimiento del Panel de Inspección es un cambio críticode políticas en este sentido, que transforma las dinámicas internas de los procesos de adopción dedecisiones en el Banco. Aun siendo importante este avance, aún es necesario incorporar los derechoshumanos en las políticas y procedimientos.Palabras clave: Banco Mundial, Panel de Inspección, proyectos, trasparencia, responsabilidad,reglas y procedimientos.